Annotation, phylogeny and expression analysis of the nuclear factor Y gene families in common bean (Phaseolus vulgaris) - Rípodas, Carolina; Castaingts, Mélisse; Clúa, Joaquín; Blanco, Flavio; Zanetti, María Eugenia (Frontiers in Plant Science, 2015)
In the past decade, plant nuclear factor Y (NF-Y) genes have gained major interest due to their roles in many biological processes in plant development or adaptation to environmental conditions, particularly in the root nodule symbiosis established between legume plants and nitrogen fixing bacteria. NF-Ys are heterotrimeric transcriptional complexes composed of three subunits, NF-YA, NF-YB and NF-YC, which bind with high affinity and specificity to the CCAAT box, a cis element present in many eukaryotic promoters. In plants, NF-Y subunits consist of gene families with about ten members each. In this study, we have identified and characterized the NF-Y gene families of common bean (Phaseolus vulgaris), a grain legume of worldwide economical importance and the main source of dietary protein of developing countries. Expression analysis showed that some members of each family are up-regulated at early or late stages of the nitrogen fixing symbiotic interaction with its partner Rhizobium etli. We also showed that some genes are differentially accumulated in response to inoculation with high or less efficient R. etli strains, constituting excellent candidates to participate in the strain-specific response during symbiosis. Genes of the NF-YA family exhibit a highly structured intron-exon organization. Moreover, this family is characterized by the presence of upstream ORFs when introns in the 5' UTR are retained and miRNA target sites in their 3' UTR, suggesting that these genes might be subjected to a complex post-transcriptional regulation. Multiple protein alignments indicated the presence of highly conserved domains in each of the NF-Y families, presumably involved in subunit interactions and DNA binding. The analysis presented here constitutes a starting point to understand the regulation and biological function of individual members of the NF-Y families in different developmental processes in this grain legume.